(untitled) (Scientia Agropecuaria, 2021)
Throughout history, the cocoa crop (Theobroma cacao L.) has been affected by countless diseases, some of these caused by Lasiodiplodia theobromae (Pat.) Griffon & Maul. Although three Lasiodiplodia species have been reported affecting cocoa plants, L. theobromae is the most studied species both in cocoa and other crops. In recent years this phytopathogen has been gaining importance. In cocoa, L. theobromae can survive in soil and culture remains in the form of pycnidia and chlamydospores, spreading by different factors until reaching the plant tissues, remaining there as an endophyte. The pathogenic fungus can cause young twigs death (a characteristic symptom found in field conditions), fruits rot and mummification, and even vascular dieback. In general, the management of pathogens of the Botryosphaeriaceae family is complex, even more so when the pathogen is already present in the crop area. However, there are genetic, cultural, biological, chemical control measures, among others, that could be integrated and used in cocoa crops. As there is little information about L. theobromae in cocoa crops, we believe that this review will be very helpful for both technicians and researchers.